Pengaruh Layanan Bimbingan dan Konseling dengan Motivasi Belajar Peserta Didik di SMP Al Ishlah Sidamulya Cirebon - Susanto, Odi (Journal of Islamic Education Counseling, 2021)
Discussion on the effect of guidance and counseling services on the learning motivation of students at SMP Ishlah Sidamulya Cirebon. the background of the study is the importance of student motivation. Meanwhile, guidance and counseling services are a place to develop this learning motivation. This research is intended to answer the following problems: (1) How is the influence of counseling guidance services at SMP Al Ishlah Sidamulya Cirebon, (2) How much influence is the counseling guidance service on the learning motivation of students at SMP Al Ishlah Sidamulya Cirebon. This study aims to determine: 1). Is there any effect of guidance and counseling services (X), with students' learning motivation (Y). In this method the researcher uses a survey method with a simple regression formula, the research subjects are 99 respondents, using a random sampling technique. Data collection uses instruments before being used to obtain objective data, first testing the validity and reliability. The collected research data were analyzed using descriptive statistical analysis techniques. The results of this study, after testing the research hypothesis using descriptive statistical analysis with a simple regression formula. Hypothesis testing shows that there is a positive influence between counseling guidance services on the level of learning motivation of students, indicated by coefficient. rxy = 5999032692 rounded off 0, 657 at the 5% significance level and 1% = 43.16% Based on the results of this study, it is hoped that it will become material for information and input for the academic community, students, lecturers of department and study programs at the Tarbiyah Faculty of IAIN Semarang, especially to the management and teachers of Al Islahagar Middle School in encouraging students to always improve learning motivation